2021
DOI: 10.1002/macp.202100259
|View full text |Cite
|
Sign up to set email alerts
|

Melt Electrowriting of Amphiphilic Physically Crosslinked Segmented Copolymers

Abstract: Various (AB)n and (ABAC)n segmented copolymers with hydrophilic and hydrophobic segments are processed via melt electrowriting (MEW). Two different (AB)n segmented copolymers composed of bisurea segments and hydrophobic poly(dimethyl siloxane) (PDMS) or hydrophilic poly(propylene oxide)‐poly(ethylene oxide)‐poly(propylene oxide) (PPO‐PEG‐PPO) segments, while the amphiphilic (ABAC)n segmented copolymers consist of bisurea segments in the combination of hydrophobic PDMS segments and hydrophilic PPO‐PEG‐PPO segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the case of fiber diameters, PCL fibers are mostly narrower (with diameters in the range of 5 µm to 15 µm) than PLA fibers (with diameters between 15 and 25 µm). Bakirci et al 54 stated that the viscosity of a polymer melt is the parameter affecting the polymer fiber diameter in MEW process. Therefore, it can be concluded that the larger diameter of PLA fibers may be the result of higher viscosity of PLA melt compared to that of PCL melt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of fiber diameters, PCL fibers are mostly narrower (with diameters in the range of 5 µm to 15 µm) than PLA fibers (with diameters between 15 and 25 µm). Bakirci et al 54 stated that the viscosity of a polymer melt is the parameter affecting the polymer fiber diameter in MEW process. Therefore, it can be concluded that the larger diameter of PLA fibers may be the result of higher viscosity of PLA melt compared to that of PCL melt.…”
Section: Resultsmentioning
confidence: 99%
“…The dimension of these defects is negligible compared to that of the fibers but their number is relatively significant. These imperfections can be due to detachment of microphase or crystallization induced by the flow 54 .…”
Section: Resultsmentioning
confidence: 99%
“…MEW Scaffolds Printing: A custom-built MEW printer was used to fabricate scaffolds as previously described. [37] MEW was performed using medical-grade PCL (PURASORB PC 12, Lot#1 712 002 224, 05/2018 Corbion Inc, Amsterdam, Netherlands) at 21 ± 3 °C and humidity of 35 ± 12%. The following parameters were used: 77 °C; 2 bar of air pressure; 30 gauge nozzle; 4 kV voltage applied across a 1.4 mm collector distance for the triangular scaffolds.…”
Section: Methodsmentioning
confidence: 99%
“…Parameters for 200 μm box scaffolds were: 80 °C; 3 bar of air pressure; 25G nozzle; 6 kV voltage applied across a 4 mm collector distance. [37] Synthesis of Thiolated Hyaluronic Acid (HA-SH) and Polyethylene Glycol-Diacrylate (PEGDA): The synthesis of HA-SH was performed with a number of modifications from Stichler et al and has been previously described. [29] PEGDA was synthesized according to Cruise et al [30,38] HA-SH was obtained as white foam after freeze drying.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation